Implementasi Pembelajaran Kreatif Berbasis Aktivitas Interaktif dan Diferensiasi untuk Meningkatkan Minat Belajar Siswa Kelas V–VI di SD Negeri Sedayu, Kec. Gemuh, Kab. Kendal - Solekhan, Ahmad; Mughist, M. Sahlul; Nafisah, Lubna Aula; Fuadz, M. Nadziful; Muarif, Tri Shohibul; Kartikasari, Yuni; Wafiroh, Vina Sa’idatul; Nahzdia, Ahmad Rizqi; Hayati, Arina Hakikiyatal; Atmina, Lia Nur; Rozaq, Abdul; Ma’rifatun, Viana; Munadhifah, Siti; Maskur, Ali; Wibowo, Frendi Suryo (Jurnal Pengabdian Kepada Masyarakat, 2026)
Learning interest is a key factor in determining student engagement and academic success in elementary education. Preliminary observations at SD Negeri Sedayu, Gemuh District, Kendal Regency revealed varying levels of learning interest and suboptimal participation among fifth and sixth-grade students due to the dominance of conventional teaching methods. This community service program aimed to implement creative learning based on interactive activities and differentiated instruction to enhance students’ learning interest. The study employed a descriptive quantitative and qualitative approach using classroom observations, interviews, a 20-item learning interest questionnaire (α=0.87), achievement tests, and documentation. The intervention included educational games, collaborative discussions (think–pair–share and simplified jigsaw), mini projects, and tiered assignments tailored to students’ abilities. The results indicated a 34.8% increase in learning interest with a moderate normalized gain, active participation reaching 82.6%, and learning mastery of 85.7%. These findings demonstrate that creative-interactive and differentiated learning effectively enhances student engagement, intrinsic motivation, and conceptual understanding in elementary education. The model is feasible for replication with contextual adjustments and strengthened teacher capacity.